Poly (N-vinyl-2-pyrrolidone-co-acrylic acid): Comparing of Traditional Heating and Microwave-Assisted Free Radical Polymerization - Kizilbey, Kadriye; Derman, Serap; Mustafaeva, Zeynep (CHEM SOC PAKISTAN, 2013)
In organic chemistry microwave irradiation has become a common heat source and the use of microwave irradiation is also increasingly studied for polymerization reactions. Polymers have been synthesized at long reaction times by classical thermal methods. In contrast, microwave-assisted polymer synthesis is a well-known and most useful method, which is requiring shorter reaction times. In this study, our aims are to compare THPS and MAPS methods between themselves, and investigate the effect of temperature in MAPS method at different parameters such as reaction times, weight average molecular weight (M-w), polydispersity index (PDI), hydrodynamic radius (Rh), intrinsic viscosity ([eta]) and Mark Houwink equation constant (a) of copolymers. Firstly we synthesized N-vinyl-2-pyrrolidone-acrylic acid copolymers [P(VP-co-AA)] both with traditional heating polymer synthesis (THPS) and microwave-assisted polymer synthesis (MAPS) method comparatively in this study. Secondly, to research temperature effect on MAPS method in addition to microwave irradiation power, polymer synthesis at 40 degrees C, 50 degrees C and 80 degrees C were tried. For analyzing of copolymers Fourier Transform Infrared (FT-IR) spectroscopy and Gel Permeation Chromatography (GPC) system with four detectors were used.
Keywords: Microwave irradiation; radical polymerization; weight average molecular weight (M-w); polydispersity index (PDI); poly(N-vinyl-2-pyrrolidone-co-acrylic acid); ACRYLIC-ACID; DRUG; COMPLEX; Chemistry